INFLUENCE OF THE COMPOSITION EVOLUTION OF WASTE COMPUTER MOTHERBOARDS ON THEIR RECYCLING STRATEGY - DORNEANU, Sorin-Aurel; AVRAM, Alexandru-Andrei; MĂRINCAŞ, Alexandru-Horațiu; COTOLAN, Nicoleta; FRENŢIU, Tiberiu; ILEA, Petru (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Even if the mobile devices gain more popularity comparing to the desktop personal computers (DPCs), the last ones are still intensively used where highly computing or storage capabilities are required. Because the replacing rate of DPCs are very high, the amount of obsolete equipments is also huge, reclaiming adequate efficient and ecological recycling techniques. In this field, the main efforts are focused on the DPCs motherboards (DPCMBs) recycling because, even if they represent only 5 to 10% from the DPCs weight, they concentrate up to 80% from the recoverable value. By accounting the DPCMBs' traditional and incipient recycling technologies, it is obvious that none of them can solve alone the problem of this waste type. In this context, during the present work, the composition evolution of 10 DPCMBs released between 1998 and 2008 was evaluated and analyzed, the obtained results being used to design a feasible and eco-friendly combined strategy for integral DPCMBs recycling.